La imagen corporal y depresión en adultos y adultos mayores practicantes de Danza Movimiento Terapia (DMT) - Castillo García, Leslie Sophia (2021)
Forgetfulness of body image (BI) when there is depression is presented and investigated in adults and elderly dance movement therapy (DMT) practitioners. Body Image is presented as one that attributes a psychological meaning to the body, while depression as a psychiatric syndrome described by 10 symptoms. Thus, the aim of this work is to carry out a revision study of the relationship between the two variables described in adults and elderly DMT practitioners. For this, the databases of Scopus, ProQuest and Ebsco were used, from which 7 representative articles on the subject were selected between the years 2000 and 2020. The results of the analyzed research suggest an indirect and proportional relationship between body image and depression in the indicated population. Finding them useful for making visible an urgent need to resolve and investigate in the field of clinical psychology. What is indicated in the results is concluded, as well as the incidence found in women belonging to a clinical population stands out.